(untitled) (Journal of the College of Basic Education, 2024)
20 clinical isolates of various wound infections were collected and biochemical tests were conducted to diagnose Staphylococcus aureus isolates. The inhibitory effectiveness of silver nanoparticles that were synthesized using the etch diffusion method against Staphylococcus aureus isolates was studied at concentrations (64000, 32000, 16000, 8000, 4000, 2000) micrograms/ ml, and it was found that the concentration that inhibited the growth of 18 was 4000 micrograms/ml. The minimum inhibitory concentration (MIC) and the minimum lethal concentration (MBC) were studied against the bacterial isolates at concentrations (2550, 6400, 3200, 1600, 800, 400, 200, and 100 micrograms/ml). It was found that the minimum inhibitory concentration of the synthetic nanoparticles was 100 micrograms/ml for a total of 15 isolates, while the minimum lethal concentration (MBC) was 200 micrograms/ml. The toxicological effectiveness of the biosynthetic silver nanoparticles was studied and it was found that the best concentration that did not cause lysis of red blood cells was 750 and 375 micrograms/ml.